Group Dynamics and Student Self-Efficacy in Online Science Learning during the COVID-19 Pandemic - Ari Widodo; Diana Rochintaniawati; Linda Kusumawati (Jurnal Penelitian Pendidikan IPA, 2021)
The complex problems of online learning in synchronous and asynchronous because of a reduction in the social life of students. It is necessary to do collaborative learning to observe the dynamics of the interactions in groups during learning. The purpose of this study was to observe group dynamics and student self-efficacy during online learning. The study uses descriptive qualitative methods with data triangulation through observations, interviews and surveys. Junior high school research subjects used the discussion method with asynchronous learning on WhatsApp group (WAG). The high school subjects used the discussion method with synchronous learning on the WAG. Aspects that are observed in group dynamics are the division of roles in groups, leadership, contributions when presenting ideas or ideas, contribution to task work, and interdependence in groups. Self-efficacy was observed using indicators of mastery experience 78% junior high school and 73.3% high school, vicarious experience 76.5% junior high school and 78.1% high school, verbal persuasion 71.4%, physiological and affective states 75.6%. The average percentage of students' self-efficacy was in the medium category, namely 74.2% for junior high school and 75.6% for senior high school